Sedimentation Process of TiO2 Nanoparticles in Aqueous Solution - Ariyanti, Dessy; Purbasari, Aprilina; Lesdantina, Dina; Saputro, Erwan Adi; Gao, Wei (Reaktor, 2022)
TiO2 nanoparticles, a semiconductor photocatalyst is widely used in various applications especially for water treatment. The common problems for the application are separating the nanoparticles from the water body and recovering it to be reused. This research was conducted to investigate the aggregation and sedimentation properties of TiO2 nanoparticles via chemical addition. The experiment was carried out for 5 hours by varying the pH, ionic strength, and the addition of organic matter such as rhodamine B, methylene orange, and humic acid. The results indicate that pH and ionic strength greatly affect the TiO2 sedimentation process. Sedimentation can be formed properly when the solution is at pH 1 and 14, this happens because pH is close to the isoelectric point. Meanwhile, ionic strength with a concentration of 0.1 M gave the most optimal results in TiO2 sedimentation. In the presence of ionic strength with the appropriate concentration, the thickness of the electrical double layer particles can be reduced so the attractive force increases and sedimentation occur. Meanwhile, in the presence of organic matter, rhodamine B, methylene orange, and humic acid did not significantly affect the formation of TiO2 sedimentation.Keywords: titanium dioxide, sedimentation, ionic strength, isoelectric point, water treatment